Financing needs and financial management practices of banana (Musa balbisiana) farmers in Inopacan, Leyte - Caintic, Pauline S.; Salabao, Analita A.; Tambis, Marlon M. (Annals of Tropical Research, 2018)
This study investigated the financing needs and the financial management practices of banana farmers in Inopacan, Leyte, the relationship between financial management practices to profitability and the relationship of the various socio-demographic variables to the relevant financial management practices. The relevant financial management practices considered in this study were those found to be significantly related to profitability. Results showed that limited capital for labor and the occurrence of pests and diseases particularly bugtok, which is caused by a bacterium called Ralstonia solanacearum, were among the major problems expressed by the banana farmers that need financing. Financial management practices such as monitoring the status of loan and financial planning and budgeting were widely practiced by the farmers. Out of the 25 farmer-respondents who availed of loan, 21 of them monitored the status of their loans. More than half of them also practiced financial planning and budgeting of their income and loan. The multiple linear regression analysis revealed that monitoring financial budgets and comparing farm profitability with that of other farms or benchmarking are significantly and positively related to profitability. The logistic regression analysis showed significant relationships of household size and being able to avail credit with the relevant financial management practices. The results imply that farmers who have more household members and who have availed of credit are more likely to monitor financial budgets and/or compare profitability with other farms.